CORE LOSS SEPARATION TESTING IN TRANSFORMERS 1 PHASE 220/48V - Maharani Putri; Ibnu Hajar; Abdullah Abdullah (CERED Indonesia Institute, 2021)
This test aims to calculate the loss of the core hysterisis and navel current (Eddy Current) separately, and to determine the effect of frequency and load flow on the loss of the transformer core. The first test is done by determining the frequency value of 25 Hz and voltage 110 V. Then the second test by determining the frequency value of 50 Hz and voltage 220 V. From the results of the pergukuran and calculation obtained at the frequency of 25 Hz, hysterisis loss = 4 watts, and eddy current loss = 0. While at a frequency of 50 Hz, hysterical loss = 8 Watts and eddy current loss = 0. The greater the frequency of sources given to a transformer, the greater the core loss to the transformer. Similarly, the greater the current flowing to the transformer, the greater the core loss. Core loss is proportional to current, this causes if there is a change in current it will greatly affect the core loss.